Spectral and statistical evaluation of the properties of the vibration measured at the base of an automotive seat for non-Gaussian random noise synthesis - Damián González; R. López-Valcarce (Int. Conf. on Noise and Vibration Engineering, ISMA-USD 2018, 2018)
The first step in the definition of the specifications for the vibration tests of any automotive component is the recording and evaluation of the properties of the input vibration during field measurements. In this paper, we explore the properties of the vibration measured at the base of the driver seat when driving through different surfaces, with the purpose of defining a model for non-Gaussian random vibration testing. The recorded acceleration signals are first transformed to a 6 Degree of Freedom (DOF) space, and then segmented into stationary sections that are later analyzed. The non-Gaussian nature of the recorded vibration is demonstrated through different Gaussianity hypothesis tests, and the distribution of the third and fourth order moments, as well as the crest factor, are computed and analyzed. The second-order  spectral content reveals significant correlation at specific frequencies, while the significance of third order polyspectra is checked through hypothesis testing. Based on our observations, a practical definition of the random process is proposed based on second-order spectral content, univariate kurtosis and crest factor levels.
Keywords: random vibration